(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The research concerns artificial intelligence in the agricultural sector, with a focus on ‘food sovereignty’, as a synthesis of different constitutional values (right to health, duty of rational land use, cultural rights, etc.). Above all, food poverty and environmental risks will be considered as vulnerabilities which intersect with other forms of social disadvantage. In particular, central to the analysis is the collection and processing of environmental and land data by agricultural technology providers. The research aims to recommend measures to ensure equitable data sharing regimes, based on farmers’ and peasants’ self-determination, but also general interests involved in agricultural data sharing.